ANALISIS DAN PERANCANGAN ULANG DESAIN USER INTERFACE UNTUK MENINGKATKAN USER EXPERIENCE PADA APLIKASI IPUNAS MENGGUNAKAN METODE GOAL DIRECT DESIGN(GDD) - Rifdah Nisrina Hiryan (2023)
The National Library of the Republic of Indonesia has launched a digital library application called iPunas which aims to increase public interest in literacy, because books lent by National Library are available electronically in various categories. so that users can access the iPunas application anytime, anywhere and users can also interact with other users. According to Republika.co.id, the iPusnas application has 52,859 digital titles and 635,377 reading collections. Widodo said, as of July 8 2020, the number of books borrowed was 52,912 books, and a total of 7,147,651 books borrowed. At the same time, the number of people queuing for books reached 410,312. However, the observation results show that iPusnas user ratings and reviews on the IOS App Store, iPusnas rating and review values are 2.8 points and on Playstore with a rating of 3.8 with a maximum rating 5. Ratings and user review scores lead to an evaluation of the iPusnas application. Therefore the researcher wants to further analyze what problems are faced by users. iPunas and Testing the design by distributing questionnaires to general respondents as many as 307 people getting a score of 80 out of 100, if it is projected into the SUS score rating then a score of 80 gets a B adjective rating Good rating and conducts interviews with UI/UX experts to validate that the design has been in accordance with applicable regulations.